Expression and characterization of a novel human recombinant factor IX molecule with enhanced in vitro and in vivo clotting activity. Issue 5 (May 2015) - Perot, Eloïse; Enjolras, Nathalie; Le Quellec, Sandra; Indalecio, Alice; Girard, Jonathan; Negrier, Claude; Dargaud, Yesim
Abstract Introduction Hemophilia B is an inherited X-linked recessive bleeding disorder, due to a defect in human factor IX (FIX). The main treatment for hemophilia B is replacement therapy using FIX concentrates. Prophylactic treatment in severe hemophilia B is very effective but is limited by cost issues. Production of a recombinant FIX (rFIX) with enhanced clotting activity, offering the possibility of fewer infusions and fewer costs with similar efficacy, is one of the current challenges for hemophilia B treatment. The present study focused on an important amino acid sequence known to be involved in the interaction of activated FIX (FIXa) with its cofactor, activated factor VIII (FVIIIa). Materials and Methods Using site-directed mutagenesis of glutamate E410 (c240, chymotrypsin numbering), four recombinant FIX-E410 (E410H, A, L and N) mutants were developed and produced by the human hepatoma cell line Huh-7. Results The in-vitro clotting activity of mutant FIX molecules was 3 to 5-fold higher than wild-type recombinant FIX (FIX-WT). FIX-E410H compound showed the highest in-vitro procoagulant activity. Enhanced specific activity was confirmed using thrombin generation assay. FIX-E410H induced 5.2-fold higher thrombin generation than FIX-WT. In hemophilia B mice, we observed significantly higher in-vivo clotting activity and thrombin generating capacity with FIX-E410H compared to FIX-WT. We demonstrated that increased procoagulant activity of FIX-E410H was mainly explained by 2.5- fold enhanced affinity of the mutant for human FVIIIa. Conclusion We have engineered and characterized four improved FIX proteins with enhanced in-vitro and in-vivo activity. Future studies are required to evaluate the immunogenicity of FIX-E410.